Decrees Nos. : 184-185-186 of the year 2017 concerning the rules governing the payment of the monthly special raise and exceptional cost of living allowance = القرارات أرقام 184-185-186 لسنة 2017 بشأن قواعد صرف العلاوة الخاصة والعلاوة الاستثنائية - Egypt; The middle east library for economic services, translator. (2025)
Ministry of finance decree no. 184 of the year 2017 concerning the rules governing the disbursement of the exceptional cost of living allowance prescribed as per law no. 79 of the year 2017 to those who are addressed by the law on civil service promulgated by law no. 81 of the year 2016 and the rules governing the disbursement of the periodic raise prescribed therefor -- Ministry of finance decree no. 185 of the year 2017 concerning the rules governing payment of the monthly special raise determined according to law no. 77 of the year 2017 to state servants who are not addressed by the law on civil service promulgated by law no. 81 of the year 2016 -- Ministry of finance decree no. 186 of the year 2017 concerning the rules governing the disbursement of the exceptional cost of living allowance prescribed as per law no. 78 of the year 2017 to the state servants who are not addressed by the law on civil service promulgated by law no. 81 of the year 2016 وزارة المالية قرار رقم 184 لسنة 2017 بشأن قواعد صرف علاوة الغلاء الاستثنائية المقررة بالقانون رقم 79 لسنة 2017 للمخاطبين بأحكام قانون الخدمة المدنية الصادر بالقانون رقم 81 لسنة 2016 وقواعد صرف العلاو الدورية المقررة لهم -- زارة المالية قرار رقم 185 لسنة 2017 بشأن قواعد صرف العلاوة الخاصة الشهرية المقررة بالقانون رقم 77 لسنة 2017 للعاملين بالدولة من غير المخاطبين بأحكام قانون الخدمة المدنية الصادر بالقانون رقم 81 لسنة 2016 – وزارة المالية قرار رقم 186 لسنة 2017 بشأن قواعد صرف علاوة غلاء استثنائية المقررة بالقانون رقم 78 لسنة 2017 للعاملين بالدولة من غير المخاطبين بقانون الخدمة المدنية الصادر بالقانون رقم 81 لسنة 2016